Delineating the Relationships Between Motor, Cognitive-Executive and Psychiatric Symptoms in Female FMR1 Premutation Carriers - Hocking, Darren R.; Loesch, Danuta Z.; Stimpson, Paige; Tassone, Flora; Atkinson, Anna; Storey, Elsdon (Frontiers in Psychiatry, 2021)
Introduction: Premutation expansions (55 to 200 CGG repeats) of the Fragile X Mental Retardation 1 (FMR1) gene on the X chromosome are associated with a range of clinical features. Apart from the most severe - Fragile X-Associated Tremor/Ataxia Syndrome (FXTAS) - where the most typical white matter changes affect cerebellar peduncles, more subtle changes may include impairment of executive functioning, affective disorders and/or subtle motor changes. Here we aimed to examine whether performance in selected components of executive functioning is associated with subclinical psychiatric symptoms in non-FXTAS, adult females carrying the FMR1 premutation. Methods and Sample: A total of 47 female premutation carriers (sub-symptomatic for FXTAS) of wide age range (26 to 77 years; M=50.3; SD=10.9) were assessed using standard neuropsychological tests, three motor rating scales and self-reported measures of psychiatric symptoms using the the Symptom Checklist-90-Revised (SCL-90-R). Results: After adjusting for age and educational level where appropriate, both nonverbal reasoning and response inhibition as assessed on the Stroop task (i.e. the ability to resolve cognitive interference) were associated with a range of primary psychiatric symptom dimensions, and response inhibition uniquely predicted some primary symptoms and global psychiatric features. Importantly, lower scores (worse performance) in response inhibition were also strongly correlated with higher (worse) scores on standard motor rating scales for tremor-ataxia and for parkinsonism. Conclusion: These results provide evidence for the importance of response inhibition in the manifestation of psychiatric symptoms and subtle tremor-ataxia motor features, suggestive of the presence of early cerebellar changes in female premutation carriers.